2015
DOI: 10.3109/13880209.2014.976713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofin vitroantipsoriatic activity of selected Indian medicinal plants

Abstract: Context: Phyllanthus simplex Retz. (Phyllanthaceae), Crotolaria juncea Linn. (Leguminosae), Leucas aspera Linn. (Lamiaceae), and Vitex glabrata R.Br. (Verbenaceae) are well-known Indian medicinal plants. Different parts of these plants are used for healing purposes traditionally in the treatment of psoriasis and various other disorders. This prompted us to assess the antipsoriatic activities of these plants. Objectives: Petroleum ether and ethanol extracts of the selected plants, i.e., P. simplex (whole plant)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In HaCaT cells, the extracts inhibited lipid peroxidation and NO production. This suggested that the antioxidant mechanism contributes to the anti-psoriatic activity of the extracts 32 .…”
Section: Aqueous Extracts Of Psoralea Corylifolia Andmentioning
confidence: 99%
“…In HaCaT cells, the extracts inhibited lipid peroxidation and NO production. This suggested that the antioxidant mechanism contributes to the anti-psoriatic activity of the extracts 32 .…”
Section: Aqueous Extracts Of Psoralea Corylifolia Andmentioning
confidence: 99%
“…Whorls are terminal, large and axillary, about 2.5cm in diameter and crowded with white bell shaped flowers. Calyx is variable, with an upper lip and short, triangular teeth [23].…”
Section: Leucas Asperamentioning
confidence: 99%